Corona in the pens of poets; reading of the poem“only ten possibilities” by Mohammed Amine Saidi (مجلة إحالات, 2026)
The corona epidemic is one of the most dangerous epidemics that have afflicted humanity in this era ; and the corona crisis has raised questions of existential anxiety ; where is this express train taking us? What will happen for humanity due to these sudden transformations ?Accordingly ; this research paper attemps to reveal the socio-psychological representations ofthe epidemic and the ontological interactions in a poem « Only ten possibilities » by the poetMohammed Amine Saidi.